CODE-SWITCHING AS A PEDAGOGICAL TOOL IN ENGLISH LANGUAGE TEACHING - Kdirbayeva Sevara Berdimuratovna (TADQIQOTLAR, 2026)
Annotation:This  article  examines  the  pedagogical  role  of  code-switching  in English  Language  Teaching  (ELT),  particularly  in  English  as  a  Foreign  Language (EFL)  classrooms.  In  multilingual  educational  environments,  teachers  and  learners frequently alternate between the target language and the native language to facilitate comprehension,  classroom  interaction,  and  emotional  support.  While  traditional language teaching approaches often discouraged the use of the first language in English instruction,  recent  sociolinguistic  and  pedagogical  research  increasingly  recognizes code-switching  as  a  valuable  instructional  strategy.  Drawing  on  methodological literature,  applied  linguistics  research,  and  classroom  observations  in  Uzbek educational  contexts,  this  article  analyzes  how  code-switching  supports comprehension, reduces anxiety, increases participation, and enhances communicative competence  among  EFL  learners.  The  study  also  discusses  the  cognitive  and sociolinguistic dimensions of code-switching and its role in multilingual classrooms.